Clinical management of breastfeeding: the role of nurses in the Neonatal Intensive Care Unit - Suzana de Souza Baptista; Valdecyr Herdy Alves; Rosangela de Mattos Pereira de Souza; Diego Pereira Rodrigues; Amanda Fernandes do Nascimento da Cruz; Maria Bertilla Lutterbach Riker Branco (Universidade Federal de Santa Maria, 2015)
Aim: to understand the clinical management of breastfeeding performed by nurses in the Neonatal Intensive Care Unit (NICU) of the University Hospital Antônio Pedro, Universidade Federal Fluminense. Method: a descriptive, exploratory study with qualitative approach, through semi-structured interviews with 11 nurses working in this Unit, whose statements were submitted to content analysis in the thematic mode. Results: two categories emerged: the guidance strategies of nurses in the clinical management of breastfeeding in the NICU; and Network of promotion and support for nursing mothers at hospital discharge: a path to successful breastfeeding. Both categories focus on the guidelines as a strategy for encouraging and supporting breastfeeding. Final considerations: nurses trained and sensitized to the practice of clinical management of breastfeeding contribute to the support of breastfeeding and coping with early weaning